PENGARUH KARAKTERISTIK DEWAN KOMISARIS TERHADAP CSRD PERUSAHAAN BUMN (Studi pada Perusahaan BUMN yang terdaftar di Indonesia Periode 2020-2022) - Krisna Putra, Benedictus; Utomo, Dwi Cahyo (Diponegoro Journal of Accounting, 2024)
This study aims to investigate the influence of the characteristics of the board of commissioners on the CSRD of state-owned enterprises (SOEs) in Indonesia. Furthermore, this research attempts to examine the impact of the characteristics of the board of commissioners, measured by using political connections within the board of commissioners, commissioners board meetings, and subcommittee of the board of commissioners. This study utilizes secondary data sourced from the annual reports and sustainability reports of SOEs published on the company's official website. By applying the purposive sampling method, a sample of 72 SOEs registered with the BPS - Statistics Indonesia and publishing annual and sustainability reports for the period 2020-2022 was obtained. The data analysis in this study was conducted using the multiple linear regression method. This study found that political connections within the board of commissioners and commissioners board meetings have a positive and significant influence on CSRD in SOEs. However, the subcommittee of the board of commissioners actually has a negative and significant impact on the CSRD of SOEs. Nevertheless, this research has limitations regarding a limited population and sample size of companies, coverage that only focuses on one aspect so that several hypotheses are rejected, as well as subjectivity in assessing CSRD due to a lack of clear information in the sustainability reports of SOEs.